Competitive Stripping of Multi-Organic Pollutants from Contaminated Water in Bubble Column Semi-Batch (Journal of Engineering, 2014)
Air  stripping  for  removal  of  Trichloroethylene  (TCE),  Chloroform  (CF)  and  Dichloromethane (DCM) from water were studied in a bubble column (0.073 m inside dia. and 1.08 m height with several sampling ports). The contaminated water was prepared from deionized water and VOCs. The presence of VOCs in feed solution was single, binary or ternary components. They were diluted to the concentrations ranged between 50 mg/l to 250 mg/l. The experiments were carried out in batch experiments which regard the bubble column as stirred tank and only gas was bubbled through stationary liquid. In this case transient measurements of VOC concentration in the liquid phase and the measured concentration profiles were modeled by bubble aeration model (BAM) to fit the experimental data fairly well. The results from batch experiments show that the removal efficiency of VOCs increases with increasing gas flow rate or gas holdup. It is found a pH=10 give the best removal rate, but all experiments were adjusted at pH=8 which allow to study other operating conditions. TCE is being removed faster than the other two components for all systems and a single component was removed faster than binary or ternary system. The KLa values were evaluated by fitting the BAM to the experimental data. It is found that KLa increased with increasing gas flow rate and TCE exhibits the highest KLa values.